Ketahanan Biokimia Tanaman Cabai terhadap Begomovirus Penyebab Penyakit Daun Keriting Kuning - Rokhana Faizah; Sriani Sujiprihati; Muhamad Syukur; Sri Hendrastuti Hidayat (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2012)
Plant biochemical resistance towards virus infection can be evaluated through measurement of salicylic acid accumulation and peroxidase concentration. A research was conducted to study biochemical resistance of chillipepper to infection of Pepper yellow leaf curl Begomovirus (PYLCV) the causal agent of pepper yellow leaf curl disease. Virus inoculation was done using insect vector, Bemisia tabaci. Salicylic acid accumulation and peroxidase concentration on 6 chillipepper genotypes (35C2, IPB C15, IPB C26, IPB C10, IPB C14, dan IPB C12) was measured 120 h after inoculation. The results showed that salicylic acid accumulation and peroxidase concentration were higher on plants after virus infection. Susceptible genotypes (35C2, IPB C15, IPB C26) tend to have higher salicylic acid accumulation and peroxidase concentration than those of resistant genotype (IPB C12). Positive correlation was observed between biochemical resistance (salicylic acid accumulation) and structural resistance (length of palisade meshophyll cell).Key words: Begomovirus, Pepper yellow leaf curl virus, peroxide enzyme, resistance mechanism, salicylic acid